Comparison of the characters of the plaque-purified viruses from foot-and-mouth disease virus O/JPN/2000 - Morioka, K.(National Inst. of Animal Health, Kodaira, Tokyo (Japan)); Fukai, K; Ohashi, S; Sakamoto, K; Tsuda, T; Yoshida, K (Journal of Veterinary Medical Science, 2008)
At least two biotypes were observed at the 2nd passage stage after the isolation of Foot-and-mouth disease Virus (FMDV) O/JPN/2000 strain. These 2 types of viruses differed from their plaque phenotypes and were distinguishable by using a monoclonal antibody (MAb) 64G8 that was made for the FMDV O/JPN/2000 strain. One of these 2 biotypes formed small plaque (SP) and with immuno staining showed a positive reaction to MAb 64G8, while the other formed clear large plaque (LP) and did not react with MAb 64G8. The amino acid sequences of the capsid coding region (VP1-VP4) of the SP virus (SPV) and the LP virus (LPV) revealed two substitutions on the 133rd amino acid in VP2, and the 56th amino acid in VP3. These amino acid changes of SPV and LPV are Asn to Asp, Arg to His, respectively. The Arg of the 56th amino acid in VP3 that have been known as critical position of cell culture adapted virus. Only LPV showed high pathogenicity in suckling mice, and its LDsub(50) was calculated to be about 10E2TCIDsub(50)/0.1 ml. These results showed that the SPV that existed at the 2nd passage stage from isolation was a low virulence virus, which may suggest why the pathogenicity of O/JPN/2000 did not show clear symptoms in infected cattle.